Constituents of the Zingiberaceae. X Diastereomers of [7-Hydroxy-5-methoxy- 2-methyl-2-(4′ -methylpent-3' -enyl)- 2 H-chromen-8-yl][3 -methyl-2″ (3″ -methylbut-2 -enyl)-6″ -phenylcy clo- hex-3″-enyljmethanone (Panduratin B), a Constituent of the Red Rhizomes of a Variety of Boesenbergia pandurata - Orasa Pancharoen (2018)
Spectroscopic studies have established that panduratin B1 and panduratin B2, isolated from the red rhizomes of a variety of Boesenbergia pandurata (Roxb.) Schltr., are the diastereomers (2RS, 1″RS, 2″SR, 6″RS)- and (2RS, 1″SR, 2"″ RS, 6″"SR)-[7-hydroxy- 5-methoxy-2-methyl-2-(4′-methylpent-3′-enyl)-2H-chromen-8-yl][3″-methyl-2″-(3″″-methylbut- 2″ ′ -enyl)-6″-phenylcyclohex-3″-enyl]methanone. A synthesis of panduratin B mixture has been achieved by chromenylation of panduratin A. © 1987 ASEG.